IMPROVING THE STUDENTS’ ABILITY IN VOCABULARY MASTERY BY USING ENGLISH SONG AT THE NINTH GRADE STUDENTS OF SMP NEGERI 1 ONOHAZUMBA - Tetema Telaumbanua (Jurnal Education and Development, 2020)
Vocabulary is a language that is important thing to be mastered by the students in learning a foreign language because it is foundation for other language components such as pronunciation, spelling, meaning, and grammar. In addition, students vocabulary mastery academically is needed language learning, because it is essential to be succesfully in reading, listening, speaking, and writing. However, many students of SMP Negeri 1 Onohazumba were unable to master in learning the component of English language because the low of vocabulary. Therefore this research is aiming to improving the students ability in vocabulary mastery by using English Song at the Ninth Grade Students of SMP Negeri 1 Onohazumba. This resesarch was designed by using Classroom Action Research (CAR) which was done in two cycles. In collecting the data needed, observation paper and test were applied as the resesarch instruments. Based on the data were analyzed, shows that the result of the researcher’s observation paper in meeting I was 63.75%. Likewise, meeting II was 87.5%. Next, cycle two in the first meeting was 93.75% and in the second meeting was 100%.While the result of students observation paper of students activities in cycle I in meeting I was 63.79% while in the second meeting was 76% and cycle two in the first meeting was 85% and second meeting was 93.71%. Furthermore, the students test result in cycle I was 53.75%while in cycle II was 71%. Based on the research findings, it can be concluded that teaching vocabulary by using English Song at the Ninth Grade Students of SMP Negeri 1 Onohazumba was applicable to improve the students ability in Vocabulary Mastery.